Caregivers' understanding of ingredients in drinks served to young children: Opportunities for nutrition education and improved labeling - Jensen Madrigal, Melissa Lorena (2021)
Background: Against expert recommendations, sugar-sweetened beverages, especially fruit drinks, are consumed by young children. Misperceptions about drink ingredients and healthfulness can contribute to caregivers’ provision. Objectives: To assess caregivers’ reasons for serving sweetened fruit-flavored drinks and unsweetened juices to their young children (1–5 y) and perceptions of product healthfulness and drink ingredients. Methods: A cross-sectional online survey assessed participants’ (n = 1614) perceptions of sweetened fruit-flavored drinks (fruit drinks and flavored water) and unsweetened juices (100% juice and water/juice blends) provided to their child in the past month, including product healthfulness, reasons for providing, and knowledge of product ingredients [added sugar, nonnutritive sweeteners (NNSs), percentage juice]. One-factor ANOVA compared perceived healthfulness of drink categories and types of sugar and NNSs, and differences between participants who could compared with those who could not accurately identify drink ingredients. Results: Participants’ top reasons for providing sweetened drinks included child liking it, being inexpensive, child asking for it, and being a special treat. Participants perceived 100% juice as healthiest, followed by juice/water blends, flavored waters, and, lastly, fruit drinks (P < 0.05). Many participants inaccurately believed the fruit drink or flavored water they served their child most often did not contain NNSs (59.0% and 64.9%) and/or added sugars (20.1% and 42.2%), when in fact they did, and 81.3–91.1% overestimated the percentage juice in the drink. Perceived healthfulness of fruit drinks was associated with caregivers’ belief that the drink contained added sugar (P < 0.05), but not with their belief that it contained NNS; increased accuracy was associated with decreased perceived healthfulness (P < 0.05). Conclusions: Inaccurate understanding of added sugar, NNSs, and percentage juice in drinks served to young children was common and could contribute to sugary drink provision. Public health efforts should seek to improve labeling practices and revise nutrition education messages.